2020
DOI: 10.1111/wej.12613
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological impact assessment on permeable road pavement with subsurface precast micro‐detention pond

Abstract: The purpose of this paper is to study stormwater management potential of new permeable pavement with subsurface micro‐detention storage (PPDS) at low‐speed residential suburban area. The main features incorporated permeable pavement of a hollow micro cylinder precast structure with solid hexagon precast concrete as top and bottom covers. The purpose of hollow micro detention design is for rainwater holding and void between the sets is for self‐drying through the side and bottom seepage during rain. The hydrolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The storage facility had a solid-framed structure but hollow within, thus having a porosity as high as 0.9. Such a storage structure was reported by [10].…”
Section: Permeable Roadsupporting
confidence: 71%
“…The storage facility had a solid-framed structure but hollow within, thus having a porosity as high as 0.9. Such a storage structure was reported by [10].…”
Section: Permeable Roadsupporting
confidence: 71%
“…Existing flood management measures, also called low-impact development measures, include permeable pavements, green roofs, sunken green spaces, planting ditches, seepage ditches, and seepage wells [3,4]. However, more basic flood management measures typically involve cement hardening, clay, silty clay, and other materials with poor infiltration, which makes it difficult to ensure effective rainwater infiltration and runoff regulation [5,6]. us, seepage wells have been adopted to improve existing flood management measures.…”
Section: Introductionmentioning
confidence: 99%
“…This method is increasingly challenging with the occurrence of climate change phenomena as it is common for a mere one-hour rainfall to cause flash flooding. As the road is easily affected by the flash flooding scenario, this study presents an alternative design to complement the existing road system by introducing a permeable road system that could channel excess water to a water storage below the road [3], [4]. A recent study has suggested that the subsurface storage of the proposed permeable pavement system could store and convey water simultaneously [5].…”
Section: Introductionmentioning
confidence: 99%